Superficial Brachioulnar Artery (SBUA) & Persistent Median Artery (PMA) : a case report - Saharudin, Shahida; Lwin, San San; Aung, Htar Htar; Sa'at@Yusof, Azlin (2011)
Variations in the arterial pattern of the upper limbs are frequently observed. During ultrasonography with General Electric Ultrasound machine with 12L-RS linear probe on a 47-year old Malay man, superficial brachioulnar arteries (SBUA) were found bilaterally. While persistent median artery (PMA) was only found on the right forearm. Both SBUA originated 1.5 cm from the origin of the brachial arteries with diameter of 3 mm on the right and 2.8 mm on the left. On the left, it maintained its superficial position on the medial aspect of the arm and the forearm. On the right, initially it ran along the medial aspect of the arm and then coursed laterally to assume a midway position in the cubital fossa. At the elbow, it crossed anterior to the median nerve and coursed in a short distance deep to flexor carpi ulnaris muscle. Later it became superficial at the middle and distal forearm. At the wrist, both arteries ran just lateral to flexor carpi ulnaris and entered the hand with diameter of 1.6 mm. Both brachial arteries were present as their normal course and divided into radial and common interosseous arteries (CIA) approximately 2 cm distal to the elbow crease. The ulnar arteries were not found bilaterally. The right CIA gave off a PMA approximately 2.5 cm from its origin. This PMA descended medially towards the right median nerve and ran along the posterolateral aspect of the nerve. It terminated at the junction between proximal and middle thirds of forearm by fusing with the sheath of median nerve. Knowledge of these variations are clinically important in vascular surgeries and arterial flap plannings.